If $\alpha + \beta - \gamma = \pi$, and $\sin ^ 2\alpha + \sin^2\beta - \sin^2\gamma = \lambda\sin\alpha\sin\beta\cos\gamma$, then find $\lambda$.

From the first equation we get that $\sin^2\gamma = sin^2(\alpha+\beta) \text{ and } \cos\gamma = -(\alpha+\beta)$.
Putting this in the second equation, we get

$$(2-\lambda)(\tan\alpha\tan\beta - 1) = 0$$
So $\lambda =\boxed{2}$
However, the procedure that I did is very long. Is there a simpler way to solve it?


Using Prove $ \sin(A+B)\sin(A-B)=\sin^2A-\sin^2B $


$$\text{As }\sin(\pi-x)=\sin x, \sin^2\beta-\sin^2\gamma=\sin(\alpha)\sin(\beta+\gamma)$$

$$\implies\sin^2\alpha+\sin^2\beta-\sin^2\gamma=\sin^2\alpha+\sin(\alpha)\sin(\beta+\gamma) =\sin\alpha[\sin\alpha+\sin(\beta+\gamma)]$$


$$\text{Finally, }\sin(\beta+\gamma)+\sin(\beta-\gamma)=?$$

| cite | improve this answer | |

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.